Transjugular intrahepatic portosystemic shunt: Indications, complications, survival and its use as a bridging therapy to liver transplant in Western Australia. Issue 4 (9th January 2017) - Pateria, Puraskar; Jeffrey, Gary P; Garas, George; Tibballs, Jonathan; Ferguson, John; Delriviere, Luc; Huang, Yi; Adams, Leon A; MacQuillan, Gerry
Abstract: Introduction: Insertion of transjugular intrahepatic portosystemic shunt (TIPS) is an established therapeutic option to treat the complications of portal hypertension. The purpose of this study is to review the experience of a single Australian institute with TIPS and evaluation of result to emphasize the indication, aetiology of portal hypertension, prognostic factors, complications and survival. Use of TIPS as a bridge to liver transplantation was also analysed. Method: A retrospective cohort study of patients treated with TIPS at The Western Australian Liver Transplant Unit, Sir Charles Gairdner Hospital, over a period of 12 years. Kaplan–Meier method was used for survival analysis and cox‐regression analysis was used to analyse the predictors of survival. Results: Fifty‐three patients underwent TIPS between January 2000 and March 2012. The cumulative survival at 1 month, 1 year and 5 years was 90%, 70.9% and 43.9%, respectively. The predictors of survival were indication (variceal bleeding versus ascites, hazard ratio 3.19, CI 95%: 1.164–8.794, P  = 0.024) and Model of End Stage Liver Disease score (Hazard ratio 2.513, CI 95%: 1.087–5.810, P  = 0.031). Patients who underwent TIPS as a bridge to liver transplant had a 5‐year survival of 71% that is comparable to the overall survival of Western Australian liver transplant unit. Conclusion: Transjugular intrahepatic portosystemic shunt is a safe and effective method of treatment of complications of portal hypertension. TIPS can be safely used as a bridging therapy to liver transplant. Despite small number of TIPS being performed at our institute, our technical results are comparable to the institutes with bigger number of patients.